«Légende des siècles» Лесі Українки: містерія горизонтів - Кочерга, Світлана; Kocherha, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2016)
Розглянуто факти з історії написання твору, його суголосність з «Легендою віків» В. Гюго. У центрі герменевтичної інтерпретації тексту перебувають мас- штабність образу буття, профетичні ідеї поезії. Ключовою бінарною опозицією у творі визначено топоси кімнати й храму. Детально проаналізовано візію езотеричного храмового простору. The article is devoted to the one of the most enigmatic works of Lesіa Ukrainka. It was taken into account the views on the text meaning of literary critics (V. Aheіeva, R. Zhylavy, V. Matviіshyn), philosophers (O. Zabuzhko, O. Guzhva), cultural critics (E. Kononenko). The main purpose of the study is expanding range of hermeneutic interpretation of the text “Lйgende des siиcles”. The proposed interpretation is based on the use of comparative and semiotic methods. We consider the facts of text writing history and its according to the unfinished epic cycle “La Lйgende des siиcles” by Victor Hugo. The magnitude of the image of being as a movement, as well as prophetic ideas and allusions in the poetry are in the the center of the study. The topoi of a room and a temple are determined as a key binary opposition in the text. The lyrical character has the priority in self-construction coordinates (which response to “quiet room”). A temple is associated with sacredness of intellectual insight. The virtual tour to the temple in “Lйgende des siиcles” is also the search for mystical sacred sanctuary, a kind of hermeneutic Grail which is the mirror of hidden truth. There is a detailed analysis of the esoteric area of the temple organized by the requirements of religious cults. It is defined the semantic content of a number of images and symbols such as fence, gate, threshold, temple
“Lйgende des siиcles” of Lesіa Ukrainka: the Mystery of Horizons
Keywords: герменевтика; «горизонт»; структуралізм; семіотика; компаративістика; деконструкція; профетизм; езотерика; гностицизм; ініціація; hermeneutics; “horizon"; structuralism; semiotics; comparative studies; deconstruction; prophetism; esoteric; Gnosticism; initiation